Methodical recommendations for practical classes, independent work and performance of an individual task in the discipline "Marketing in anti-crisis management" - Larka, Lyudmila (National Technical University "Kharkiv Polytechnic Institute", 2024)
Methodological recommendations consist of three parts: recommendations for practical classes, recommendations for independent work, and recommendations for completing an individual task. Recommendations for practical lessons are presented in the form of a detailed lesson plan, which allows applicants to focus on the key points of the topic of the practical lesson. Discussion of given topics during practical classes allows students to practice the skills of conducting a scientific debate, substantiate their own point of view, and listen to constructive criticism. The topics of practical classes correspond to the syllabus of the discipline "Marketing in anti-crisis management". Recommendations for independent work contain tasks for independent implementation and tests, the completion of which allows students to consolidate the material of lectures and practical classes.
Keywords: anti-crisis management; marketing complex; preventive marketing; anti-crisis management system; methodical recommendations; practical classes; independent work; individual task; marketing in anti-crisis management